Effects of message framing, psychological distance, and risk perception on exercise attitude in Chinese adolescents - Wang, Xiaohua; Duan, Xiyan; Li, Shichen; Bu, Te (Frontiers in Pediatrics, 2022)
Objectives Health communication campaign that promotes physical activity may aid in reducing the prevalence of childhood and adolescent obesity in China. This study examined the effects of message framing and psychological distance on the exercise attitude of Chinese adolescents, along with the interactive role of risk perception. Methods Participants in this study were between 10 and 19 years of age. Three experiments were conducted independently. In experiment 1, 76 participants were recruited to assess the effectiveness of message manipulation. In experiment 2, 40 participants were recruited to compare the effects of gain- and loss-framed messages on the exercise attitude. In experiment 3, 37 participants were recruited to explore the interaction between message framing (gain vs. loss), temporal distance (proximal vs. distal), and risk perception (low vs. high) on the exercise attitude. Exercise attitude and risk perception were assessed by Likert-type questionnaires. Results There was a significant main effect of message framing (P < 0.05), with the gain-framed message inducing a stronger exercise attitude than the loss-framed message. There was a significant main effect of temporal distance (P < 0.05), with the proximal temporal distance condition inducing a stronger exercise attitude than the distal temporal distance condition. In addition, a significant interaction (P < 0.05) was observed, and the perception of obesity-related risk was a crucial moderator of the message framing and temporal distance. Regardless of whether they were exposed to a gain- or loss-framed message, the proximal temporal distance condition induced a stronger exercise attitude in participants with a high risk perception (P < 0.05). Conclusion Messages promoting exercise that are framed as having a near-future gain effect and that emphasize disease risks are effective in motivating adolescents to engage in physical activity.